2016
DOI: 10.1249/mss.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Physical Activity on Passive Leg Movement–Induced Vasodilation with Age

Abstract: Introduction Due to reduced nitric oxide (NO) bioavailability with age, passive leg movement (PLM)-induced vasodilation is attenuated in older sedentary subjects and, unlike the young, cannot be augmented by posture-induced elevations in femoral perfusion pressure. However, whether vasodilator function assessed with PLM, and therefore NO bioavailability, is preserved in older individuals with greater physical activity and fitness is unknown. Methods PLM was performed on four subject groups (young sedentary (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
5
17
0
Order By: Relevance
“…In the current study, we chose to include subjects that were characterized by a moderate level of physical activity to limit the potential adverse effects of skeletal muscle disuse in an attempt to primarily elucidate the effects of aging (12). Physical activity has been shown to improve NO signaling in older subjects (21,23,33), which is in line with the present finding of similar vasodilator response to passive leg movement in the two groups as this observation indicates a beneficial effect of the moderate level of physical activity on NO and cGMP bioavailability (11). Hence, the lack of effect of PDE5 inhibition on the vascular response to exercise in the older individuals may to some extent reflect an improved cGMP signaling.…”
Section: Discussionsupporting
confidence: 84%
“…In the current study, we chose to include subjects that were characterized by a moderate level of physical activity to limit the potential adverse effects of skeletal muscle disuse in an attempt to primarily elucidate the effects of aging (12). Physical activity has been shown to improve NO signaling in older subjects (21,23,33), which is in line with the present finding of similar vasodilator response to passive leg movement in the two groups as this observation indicates a beneficial effect of the moderate level of physical activity on NO and cGMP bioavailability (11). Hence, the lack of effect of PDE5 inhibition on the vascular response to exercise in the older individuals may to some extent reflect an improved cGMP signaling.…”
Section: Discussionsupporting
confidence: 84%
“…Additionally, a lack of baseline differences between the AT and UT groups may indicate similar NO concentrations in the vasculature of AT and UT groups due to vascular remodeling, which has been reported in aerobic training studies using the FMD technique (Tinken et al 2008(Tinken et al , 2010. Currently, only one study has used the PLM technique in aerobically trained individuals (Groot et al 2016) and while leg vascular function was reported to be greater using this technique, this study focused on older athletes. Interestingly, endurance-trained older adults exhibit greater arterial FMD when compared with age-matched untrained controls, a finding that is not matched when comparing young athletes and untrained controls (Montero et al 2014).…”
Section: Aerobic Capacity and Vascular Functionmentioning
confidence: 92%
“…Indeed, individuals undertaking aerobic training display substantial improvements in vascular reactivity during the initial weeks of training (Spence et al 2013;Tinken et al 2008). This improved vascular function is due to an increased bioavailability of vasodilatory components, such as NO (Groot et al 2016;Taddei et al 2000), and/or an upregulation of antioxidant defense (Azizbeigi et al 2014;Gomez-Cabrera et al 2008) that further acts to reduce the scavenging of NO (Inoue et al 1996). Highly NOmediated vascular function measures, such as the passive leg movement (PLM) technique, have strengthened this finding by revealing significantly greater leg vascular function in aerobically trained adults compared with sedentary controls (Groot et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The recent literature underlined that augmenting physical activity and fitness can protect NO bioavailability, attenuating the deleterious effects of advancing age on vascular function (Groot et al, 2016 ). Therefore, particular attention on the determination of the physical activity level is needed in order to better describe the net effect of aging and AD to the systemic vascular function.…”
Section: Discussionmentioning
confidence: 99%